The meaning and legacy of the Reformation in a global perspective. Issue 2 (20th May 2019) - Grosshans, Hans‐Peter; Nüssel, Friederike
Abstract: When reviewing the non‐European perspectives of Lutheran theology presented in the contributions of this issue of Dialog, it is easy to recognize a dominant, unifying theme and a common task in a confrontation with the new Pentecostal churches. It then makes sense to refer to the two central themes and tasks of Lutheran theology mentioned in this volume: the development of a Lutheran pneumatology in contrast to the Pentecostal/charismatic movements; and an interpretation of the Lutheran doctrine of justification that concentrates on how the pure grace and love of God can be witnessed in good works. As a future focal point of Lutheran theology, the contributions from non‐European Lutheran Christianity presented here show that the connection between the theology of the cross as a central element of the grammar of Lutheran Christianity and the dialectics of law and gospel for the interpretation of the salutary efficacy and experienceable nature of the Spirit requires further reflection.